2001
DOI: 10.1007/s11894-001-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Causes and treatment of functional dyspepsia

Abstract: Functional dyspepsia is a clinical syndrome defined by upper abdominal symptoms without identifiable cause by conventional diagnostic means. Recent studies have established that functional dyspepsia is a heterogeneous disorder in which different pathophysiologic disturbances underlie different symptom profiles. Delayed gastric emptying is associated with postprandial fullness, nausea, and vomiting; impaired accommodation is associated with early satiety and weight loss; and hypersensitivity to gastric distenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 49 publications
0
13
0
5
Order By: Relevance
“…Somit resultiert eine beschleunigte Magenpassage [31]. Diese Störung der gastralen Funktion kann mittels entsprechender Diagnostik identifiziert und quantifiziert werden.…”
Section: E Fd-patienten Weisen Eine Gestörteunclassified
“…Somit resultiert eine beschleunigte Magenpassage [31]. Diese Störung der gastralen Funktion kann mittels entsprechender Diagnostik identifiziert und quantifiziert werden.…”
Section: E Fd-patienten Weisen Eine Gestörteunclassified
“…47,48 Drugs that relax the gastric fundus [e.g., tegaserod, cisapride, sumatriptan, buspirone, clonidine, some selective serotonin reuptake inhibitors (SSRIs), and nitric oxide (NO) donors] may theoretically improve some symptoms of dysmotility-like dyspepsia (e.g., early satiety), but adequate RCTs are lacking. 49 In 2002, Hallerback et al 50 compared the efficacy of mosapride, a 5-hydroxytryptamine 4 (HT 4 )-receptor agonist, compared with placebo in the treatment of FD (Table 2) in a double-blind, prospective, multicenter, multinational study and found that treatment of FD with mosapride was not superior to placebo. On the other hand, Otaka et al 51 evaluated the efficacy of an H 2 RA (famotidine) and mosapride by randomizing FD patients to receive famotidine (20 mg/day) or mosapride (15 mg/day) for 4 weeks and demonstrated that both famotidine and mosapride had beneficial effects regardless of FD subtype or age and sex of the patient, with no significant difference in the efficacy of these two drugs in relieving FD symptoms.…”
Section: Prokineticsmentioning
confidence: 99%
“…La creciente evidencia en torno a la interrelación de diferentes factores psicosociales en la DF apoya incluir dentro de la intervención médica de esta enfermedad, la evaluación y el tratamiento psicológi-co, con el fin de incidir positivamente en la curación de los síntomas y mejorar la calidad de vida, tal como has sido sugerido recientemente (Tack et al, 2001;Tobón, Vinaccia y Sandín, 2003b).…”
Section: Evaluación Y Tratamiento Psicológicounclassified
“…Algunos autores recomiendan el empleo de ésta sólo cuando el tratamiento farmacológico falla y hay presencia de trastornos psicopatológicos (Tack et al, 2001;Tarilonte, 2002). Sin embargo, es factible que el empleo de la terapia psicológica desde el comienzo mejore de forma significativa el pronóstico y contribuya a una mejor calidad de vida en muchos pacientes.…”
Section: Tratamiento Psicológicounclassified
See 1 more Smart Citation